The Contributions of Professional Engineers at the Instituitions of Higher Learning - Zamri, Harun; Mohamad Dali, Isa; Zamri, Mohamed; Shahrum, Abdullah (Elsevier, 2012)
This paper discusses the current contributions of professional engineers (P.Es.) who have obtained their competency qualifications prior to assuming their new careers at the institutions of higher learning (IHLs). Recent surveys conducted by recruitment agencies show a wide gap between engineering graduates’ abilities and emplo yers’ expectations. This gap simply means a longer learning curve for trainee engineers expected by employers. However, most importantly, it seems that employers have to take on the job to bridge the gap. Providing training means incurring costs and resources. There are many schemes provided by multi-national company (MNC) however such schemes may not be options by small and medium enterprise (SME). Based on experience, discussion and observations, P.E.s contribute positively in the three core areas: 1) teaching and learning 2) research and publication and 3) industrial linkage.